2014
DOI: 10.1073/pnas.1413566111
|View full text |Cite
|
Sign up to set email alerts
|

Experimental basis for a new allosteric model for multisubunit proteins

Abstract: Monod, Wyman, and Changeux (MWC) explained allostery in multisubunit proteins with a widely applied theoretical model in which binding of small molecules, so-called allosteric effectors, affects reactivity by altering the equilibrium between more reactive (R) and less reactive (T) quaternary structures. In their model, each quaternary structure has a single reactivity. Here, we use silica gels to trap protein conformations and a new kind of laser photolysis experiment to show that hemoglobin, the paradigm of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 55 publications
0
62
0
Order By: Relevance
“…Finally, photolysis experiments on gel-encapsulated hemoglobin revealed that in the absence of allosteric effectors, subunits of the T quaternary structure can bind carbon monoxide (CO) at the same fast rate as subunits in the R quaternary structure, and that subunits of the R quaternary structure can bind CO with the same slow rate as subunits in the T quaternary structure. More specifically, nanosecond pulsed-laser photolysis measurements for the CO complex of hemoglobin trapped by the gel in the T quaternary structure in the absence of allosteric effectors showed that a large fraction of the photolyzed subunits bind CO at rates identical to those found for the R quaternary structure (30), whereas CO rebinding after continuous-wave (cw) photolysis of the R quaternary structure encapsulated in the gel showed the stretched exponential appearance of a fraction of subunits that bind CO at the Hill plots comparing oxygen binding curves of human hemoglobin in solution, in single crystals, in the sickle hemoglobin fiber, and encapsulated in gels as either the T or R quaternary structure (from Viappiani et al (37)). The superscripts indicate whether (þ) or not (À) saturating concentrations of allosteric effectors inositol hexaphosphate and bezafibrate are present.…”
Section: Introductionmentioning
confidence: 81%
“…Finally, photolysis experiments on gel-encapsulated hemoglobin revealed that in the absence of allosteric effectors, subunits of the T quaternary structure can bind carbon monoxide (CO) at the same fast rate as subunits in the R quaternary structure, and that subunits of the R quaternary structure can bind CO with the same slow rate as subunits in the T quaternary structure. More specifically, nanosecond pulsed-laser photolysis measurements for the CO complex of hemoglobin trapped by the gel in the T quaternary structure in the absence of allosteric effectors showed that a large fraction of the photolyzed subunits bind CO at rates identical to those found for the R quaternary structure (30), whereas CO rebinding after continuous-wave (cw) photolysis of the R quaternary structure encapsulated in the gel showed the stretched exponential appearance of a fraction of subunits that bind CO at the Hill plots comparing oxygen binding curves of human hemoglobin in solution, in single crystals, in the sickle hemoglobin fiber, and encapsulated in gels as either the T or R quaternary structure (from Viappiani et al (37)). The superscripts indicate whether (þ) or not (À) saturating concentrations of allosteric effectors inositol hexaphosphate and bezafibrate are present.…”
Section: Introductionmentioning
confidence: 81%
“…The low affinity T-state and the high affinity Rstate of Hb can be trapped by encapsulating Hb either as fully deoxygenated or fully oxygenated molecules, respectively [57,82,83,100]. Indeed, non-cooperative oxygen binding is observed both when Hb is encapsulated in the high-affinity R state or in the lowaffinity T state [57,58,82,83,85,100] (Fig. 3).…”
Section: Trapping Reaction Intermediates: Inhibition Of Conformationamentioning
confidence: 99%
“…The possibility provided by silica gel encapsulation to reduce the rate of conformational changes by orders of magnitude, increasing the kinetic separation of tertiary and quaternary relaxations [57,58,[80][81][82][83][84][85][86][87][88][89][90][91][92], has been extensively exploited by several groups to make accessible to spectroscopic investigation species that are normally poorly populated, or metastable on the time scale of solution experiments. Not surprisingly, many of these studies concern hemoglobin (Hb), myoglobin and other heme binding proteins, since the availability of a sensitive, intrinsic chromophoric signal allowed to achieve an unprecedented level of detail in the comprehension of structure-dynamic-function relationships.…”
Section: Heme Proteinsmentioning
confidence: 99%
See 2 more Smart Citations